The Influence of Social Media Marketing and Product Quality on Mykonos Perfume Purchase Decisions: The Mediating Role of Streamer Setiawan Ade - Rahmad Fauzan Hsb; Willy Yusnandar (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
The rapid growth of digital marketing has encouraged perfume companies to utilize social media and streamers to influence consumer purchasing decisions. However, previous studies have provided limited evidence regarding the mediating role of streamers in explaining how social media marketing and product quality influence purchase decisions in the perfume industry. Therefore, this study aims to analyze the influence of social media marketing and product quality on Mykonos perfume purchase decisions through the mediating role of Streamer Setiawan Ade. This study employed a quantitative approach with an associative research design involving 120 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The findings reveal that social media marketing and product quality do not have a significant direct effect on purchase decisions. However, both variables significantly influence the role of the streamer, while the streamer significantly affects consumers' purchase decisions. Furthermore, the streamer significantly mediates the relationships between social media marketing and purchase decisions as well as between product quality and purchase decisions. These findings highlight the importance of streamer credibility as a mediating mechanism in improving the effectiveness of digital marketing strategies within the perfume industry.